Interpreting experience and working memory effects on L1 and L2 morphological prediction - Lozano-Argüelles, Cristina; Sagarra, Nuria; Casillas, Joseph V. (Frontiers in Language Sciences, 2023)
The human brain tries to process information as efficiently as possible through processes like prediction. Native speakers predict linguistic information extensively, but L2 learners show variability. Interpreters use prediction while working and research shows that interpreting experience mediates L2 prediction. However, it is unclear whether advantages related to interpreting are due to higher working memory (WM) capacity, a typical characteristic of professional interpreters. To better understand the role of WM during L1 and L2 prediction, English L2 learners of Spanish with and without interpreting experience and Spanish monolinguals completed a visual-world paradigm eye-tracking task and a number-letter sequencing working memory task. The eye-tracking task measured prediction of verbal morphology (present, past) based on suprasegmental information (lexical stress: paroxytone, oxytone) and segmental information (syllabic structure: CV, CVC). Results revealed that WM mediates L1 prediction, such that higher WM facilitates prediction of morphology in monolinguals. However, higher WM hinders prediction in L2 processing for non-interpreters. Interestingly, interpreters behaved similarly to monolinguals, with higher WM facilitating L2 prediction. This study provides further understanding of the variability in L2 prediction.